IRRI-BADC launches digital tool to improve rice supply in Bangladesh - Habib, Muhammad Ashraful; Nayak, Swati; Nuruzzaman; Islam, Saidul (International Rice Research Institute, 2025)
Seed supply planning in Bangladesh has long been constrained by manual processes, fragmented data, and reactive decision-making, often resulting in mismatches between seed availability and farmers’ actual needs, especially under increasing climate risks. To address these challenges, IRRI, in collaboration with the Bangladesh Agricultural Development Corporation (BADC), the World Bank, APCU, and the PARTNER program, has initiated a digital seed demand forecasting initiative. The initiative aims to replace paper-based forecasting with a participatory, data-driven system that integrates farmer and market feedback with agro-climatic information to generate predictive, location-specific insights. Through a collaborative and inclusive approach involving policymakers, research institutions, extension services, private sector actors, and farmer groups, the platform seeks to improve demand-aligned, climate-smart seed planning. By linking field-level realities with national planning frameworks, this initiative is expected to enhance timely seed delivery, strengthen system resilience, and support Bangladesh’s food security goals.